Oryzisolibacter propanilivorax gen. nov., sp nov., a propanil-degrading bacterium - Ivone Vaz Moreira (2017)
Strain EPL6(T), a Gram-negative, motile, short rod was isolated from a propanil and 3,4-dichloroaniline enrichment culture produced from rice paddy soil. Based on the analyses of the 16S rRNA gene sequence, strain EPL6(T) was observed to be a member of the family Comamonadaceae, sharing the highest pairwise identity with type strains of the species Alicycliphilus denitrificans K601(T) (96.8 %) and Melaminivora alkalimesophila CY1(T) (96.8 %). Strain EPL6(T) was able to grow in a temperature range of 15-37 degrees C, pH 6-9 and in the presence of up to 4% (w/v) NaCl and tested positive for catalase and oxidase reactions. The major respiratory quinone was Q8. The genomic DNA had a G+C content of 69.4 +/- 0.9 mol%. The major polar lipids were phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol, and the major fatty acid methyl esters comprised C-16 : 0, C-18 : 1 omega 7c and summed feature 3 (C-16 : 1 omega 7c/iso-C-15 : 0 2-OH). Comparison of the genome sequence of strain EPL6(T) and of its closest neighbours, Melaminivora alkalimesophila CY1(T) and Alicycliphilus denitrificans K601(T), yielded values of ANI <= 84.1% and of AAI <= 80.3 %. Therefore, the genetic, phylogenetic, phenotypic and chemotaxonomic characteristics support the classification of this organism into a new taxon. Considering the genetic divergence of strain EPL6(T) from the type strains of the closest species, which belong to distinct genera, we propose a new genus within the family Comamonadaceae, named Oryzisolibacter propanilivorax gen. nov., sp. nov., represented by the isolate EPL6(T) as the type strain of the species (=LMG 28427(T)=CECT 8927(T)).